Partnership Matters in Health Services Research: A Mixed Methods Study of Practitioners' Involvement in Research and Subsequent Use of Evidence-Based Interventions. (July 2017) - Spector, Anya Y.; Pinto, Rogério. M.
Health and social service practitioners have not readily incorporated research-based behavioral interventions in HIV prevention practice due to lack of awareness, lack of training, and challenges translating research findings into practice. Practitioners' involvement in research is associated with their willingness to use research to guide practice. Likewise practitioners' personal and organizational characteristics have been shown to be associated with use of research findings in practice. Factors associated with practitioners' use of evidence-based interventions (EBIs) in HIV prevention, however are not well understood. While research involvement has been recommended to help practitioners overcome barriers to the use of EBIs, the types of research involvement that result in practitioners' actual use of EBIs is not known. This is partly because most studies are either qualitative or quantitative and ignore the voices of practitioners, which can be best unearthed with qualitative research followed by survey research including larger numbers of participants. By using a mixed methods approach, this study fills this gap by showing associations between practitioners' and organizational characteristics, specific areas of research involvement, and practitioners' use of EBIs. The use of mixed methods was extremely helpful to integrate in-depth qualitative interview data from practitioners across 10 community-based agencies providing social and health services, with cross-sectional survey data from practitioners across 24 agencies in New York City. We used a sequential approach for data collection and a concurrent approach for data analysis, content analysis of in-depth interviews, and multivariate linear regression analysis. Practitioners who performed research tasks/procedures similar to their professional duties as well as their level of education, knowledge about EBIs, and their agency capacity were all positively associated with HIV evidence–based interventions. Training practitioners in research, engaging practitioners in research tasks that resemble their professional practices, and capacity building within organizations to foster academic-research partnerships could optimize practitioners' use of EBIs.